Thickness Measurement and Sensitivity of Copper/Nickel Electroplating Results of Electrolyte Solution Temperature Variation - Islamiyati, Rizka Nuzul; Toifur, Moh.; Okimustava, Okimustava (Spektra: Jurnal Fisika dan Aplikasinya, 2024)
Currently, cryogenic thermometers are needed and one of the uses of cryogenic thermometers is to measure the temperature of food preservation flasks. Research has been conducted on the manufacture of cryogenic thermometers derived from Cu/Ni coils by electroplating process with temperature variation treatment of electrolyte solution. The purpose of this study is to determine the effect of electrolyte solution temperature variation treatment on Ni thickness and Cu/Ni sensitivity as a low-temperature sensor. Electroplating was carried out with electrolyte temperature parameters of 30˚C-70˚C, electrode distance of 4 cm, voltage of 4.5 volts, and coating time of 4 minutes. The electrolyte solution was a mixture of NiSO4 260 g, NiCl2 60 g, H3BO3 40 g, and Aquades 1000 mL. Based on the results of the study, a remarkable condition was obtained on the thickness of Ni; namely, at 40 ˚C, the thickness increased to 1.08 mm. In addition, the best temperature can produce the greatest sensitivity value in Cu/Ni coil electroplating, namely at 50 ˚C.